using f(x)=4x 2 and g(x)=6x what is g(x)-f(x)

I assume the question to be: “ Using f(x) = 4x+2 and g(x)=6x what is g(x) - f(x)? ”

Answer:

g(x) – f(x)

= 6x – (4x+2)

= 6x – 4x – 2 [breaking the brackets by distributing the minus sign]

= 2x – 2Please "best" this answer if you think it's detailed and can help you out. You can add me as a tutor for further questions. Thanks.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up